2003
DOI: 10.1007/s00454-003-2867-z
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorics of Polytopes with a Group of Linear Symmetries of Prime Power Order

Abstract: Generalizing a result of Stanley [13] on centrally symmetric polytopes, Adin [2], [3] has derived tight lower bounds for the face numbers of a rational simplical polytope equipped with a fixed-point-free linear action of a cyclic group G of prime power order. The main goal of this paper is to extend these results further by replacing Adin's fixedpoint-free condition with the assumption that the action of G is proper. As corollaries, we obtain a generalization of Adin's equivariant lower bound theorem and of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Our starting point was Stanley's result [21] asserting that a cs simplicial d-polytope P satisfies g r (P ) ≥ d r − d r−1 for all 1 ≤ r ≤ ⌊d/2⌋. However, it is worth mentioning that Adin [1] and later Jorge [12] showed that Stanley's result can be suitably extended to polytopes with more intricate symmetries. It would be very interesting to check if our techniques can be adapted to provide a characterization of polytopes that minimize g 2 in these more general settings.…”
Section: Polytopes With Other Symmetriesmentioning
confidence: 99%
“…Our starting point was Stanley's result [21] asserting that a cs simplicial d-polytope P satisfies g r (P ) ≥ d r − d r−1 for all 1 ≤ r ≤ ⌊d/2⌋. However, it is worth mentioning that Adin [1] and later Jorge [12] showed that Stanley's result can be suitably extended to polytopes with more intricate symmetries. It would be very interesting to check if our techniques can be adapted to provide a characterization of polytopes that minimize g 2 in these more general settings.…”
Section: Polytopes With Other Symmetriesmentioning
confidence: 99%
“…This suggests the possibility of arriving at properties of ∆ via investigation of the characters. In fact, work of this this flavor (using more directly the isomorphism of H * (X σ , Q) and Q[∆]/Θ in order to use additional properties of the toric variety) has been done to investigate simplicial polytopes with certain simple symmetries, see, e.g., [1], [4], and [5].…”
Section: Remarksmentioning
confidence: 99%